India and Central Asia in the new policy – «Connect Central Asia» (International relations and international law Journal, 2018)
The «new» foreign policy of India, associated with significant changes in the political course of the country, which has occurred in recent years, as well as in the external environment. India aspires to become an active factor in world politics with the help of new technologies, scientific and technological revolution. As one of the main centers of global power, India is active in the policy establishment and strengthening of regional ties with Central Asia. Convergence India with Central Asia at the present stage based on the fact that the bonds in the two decades to strengthen, relations were established at the highest political level, they are characterized by the intensity of the mutual visits of the heads of the first and important cooperation agreements. In recent years, India’s policy of «turned» towards the Central Asian region through in-depth «partnership» in political, economic and technical cooperation, «Connect Central Asia» India through a new policy.Key words: new internationalism, a new concept of foreign policy of India, «New Asianism», «Connect Central Asia», security, Central Asia.